Tunable Thermo-Responsive Properties of Hydroxybutyl Chitosan Oligosaccharide - Chen, Chong; Zhang, Weibo; Zhang, Yan; Wang, Pengjie; Ren, Fazheng (Frontiers in Chemistry, 2022)
In this paper, a simple method was used to synthesize novel thermo-sensitive hydroxybutyl chitosan oligosaccharide (HBCOS) by introducing hydroxybutyl groups to C6-OH of chitosan oligosaccharide (COS) chain. The variation of light scattering demonstrated that HBCOS had good thermo-sensitive properties and the particle size of HBCOS changed from 2.21 - 3.58 nm to 281.23 – 4162.40 nm as the temperature increased to a critical temperature (LCST). The LCST of HBCOS (10 mg/mL) decreased from 56.25 ℃ to 40.2 ℃ as the degrees of substitution (DS) increased from 2.96 to 4.66. The LCST of HBCOS with a DS of 4.66 decreased to 33.5 ℃ and 30 ℃ as the HBCOS and NaCl concentrations increased to 50 mg/mL and 4% (w/v), respectively. Variable-temperature FTIR spectroscopy confirmed that dehydration of hydrophobic chains and the transition of hydrogen bonds were the driving forces for the phase transition of HBCOS. Moreover, HBCOS was not cytotoxic at different concentrations. This work generated a novel thermo-sensitive HBCOS with tunable thermo-responsive properties and excellent biocompatibility, which may be a potential nanocarrier for the biomedical application.